Pengaruh Terpaan Iklan Layanan Masyarakat “Don’t Know? Kasih No!” oleh BCA Terhadap Sikap Pengguna Twitter/X - Joel Gerald Halomoan Hutauruk; Anter Venus; Putri Trulline (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
With the existence of social media, the distribution of public service advertisement videos has become easier. However, the rampant cases of phishing in society lately have the potential to harm users of online banking services. The purpose of this study is to determine the effect of exposure to public service advertisements on the attitudes of Twitter / X users. This study uses a quantitative approach. The choice of research method that will be used is the quantitative causality method. This study will use X / Twitter users who have watched the public service advertisement video